2021
DOI: 10.1016/j.jsxm.2020.10.020
|View full text |Cite
|
Sign up to set email alerts
|

The Informed Consent Model of Care for Accessing Gender-Affirming Hormone Therapy Is Associated With High Patient Satisfaction

Abstract: Background: There are 2 common approaches to assess an individual before commencing of gender-affirming hormone therapy (GAHT); a mental health practitioner assessment and approval or an informed consent model undertaken with a primary care general practitioner (GP). Aim: In a primary care clinic practising an Informed Consent Model of care to initiate GAHT, we aimed to firstly describe the proportion and characteristics of patients referred for secondary consultation to a mental health practitioner (MH referr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…The approach of the diagnostic model to gender affirmation healthcare has come under increased fire in recent years (Schulz 2018 ; Riggs et al 2019 ; Lipshie-Williams 2020 ; Spanos et al 2021 ). On this approach, those who seek access to gender affirming services must be granted approval by a mental health practitioner on the basis of meeting the criteria for a diagnosis of gender dysphoria or gender incongruence.…”
Section: The Diagnostic Modelmentioning
confidence: 99%
“…The approach of the diagnostic model to gender affirmation healthcare has come under increased fire in recent years (Schulz 2018 ; Riggs et al 2019 ; Lipshie-Williams 2020 ; Spanos et al 2021 ). On this approach, those who seek access to gender affirming services must be granted approval by a mental health practitioner on the basis of meeting the criteria for a diagnosis of gender dysphoria or gender incongruence.…”
Section: The Diagnostic Modelmentioning
confidence: 99%
“…Whilst the presence of some mental health disorders (particularly those with manic or psychotic features) may have an impact on an individual's capacity to provide IC, a recent meta-review showed that most clients with a severe mental disorder made appropriate decisions regarding their healthcare. 52 An Australian study 30 revealed that general practitioners needed to refer only 8% of their TGD clients to a mental health professional prior to HT initiation and most of these clients had either schizophrenia or post-traumatic stress disorder (PTSD). Over half (56%) of TGD clients in this study had a mental health condition, such as depression, anxiety, attention-deficit-hyperactivitydisorder, autism-spectrum disorder or bipolar disorder; however, this did not have an impact on their capacity to consent to HT.…”
Section: Mental Healthmentioning
confidence: 99%
“…Over half (56%) of TGD clients in this study had a mental health condition, such as depression, anxiety, attention-deficit-hyperactivitydisorder, autism-spectrum disorder or bipolar disorder; however, this did not have an impact on their capacity to consent to HT. 30…”
Section: Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Professional Association of Transgender Health (WPATH) Standards of Care, first published in 1979 and now on its seventh iteration [ 13 ], recommend universal evaluation by a mental health provider (MHP) and formal documentation that the patient is an appropriate candidate for GAH with a diagnosis of “gender dysphoria” prior to initiating care [ 14 ]. Gender dysphoria, defined in the 2013 version of the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition: DSM-5 [ 15 ], refers to emotional distress caused by the incongruence between a person’s sex assigned at birth and their gender identity.…”
Section: Introductionmentioning
confidence: 99%